Clinical Environment to Improve Operations, Medical and Surgical Applications: Study of Alternative Model of Carbon Connection of Diamond - Alaa N. Hadi; Abbas H. Mugheer; Fadhel Omran Essa; Abdulameer K. Arat; Qasim S . Kadhim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Carbon Materials, especially interesting for practical application in the different areas of science andtechnique, by virtue of the numerous unique physical and chemical properties. The popular object ofresearches presently is allotropic modification of carbon – diamond that is examined as a classic modelcrystal. One of the most effective going near research of physical and chemical properties of diamondis his study by means of preliminary computer design of the studied dielectric descriptions. The authorsof the article examine the traditional and alternative mathematical models of the electronic configurationof nonpolar valency chemical connection of diamond. Results over of design of dielectric descriptionsof resilient electronic polarization of the examined material are brought on the basis of an offer physicalinterpretation of electronic structure.